- #1
mhill
- 189
- 1
My conjecture is that using the Selberg-Delange method the next asymptotic equality holds
[tex] \sum_{n \le N } \mu (n) \sim (\sqrt n )log^{a}(n) \frac{G(c)}{\Gamma (b)} [/tex]
where a,b and c are positive constants and Gamma stands for (n-1)! , G(c) is just [tex] G(c) \zeta (c) =1 [/tex]
[tex] \sum_{n \le N } \mu (n) \sim (\sqrt n )log^{a}(n) \frac{G(c)}{\Gamma (b)} [/tex]
where a,b and c are positive constants and Gamma stands for (n-1)! , G(c) is just [tex] G(c) \zeta (c) =1 [/tex]